DECRIMINALISATION OF MASS MURDERS, RAPE AND SEXUAL VIOLENCE — A CRITIQUE OF PRESIDENT MBEKI AND PROF MAMDANI (The Strategic Review for Southern Africa, 2020)
In an opinion article titled "Courts can't end civil wars" by South African President Thabo Mbeki (1999-2008) and Prof Mahmood Mamdani of Makerere and Columbia Universities published in the New York Times (5 February 2014), the two argued that civil wars can only be ended by peace talks where former foes sit together at the negotiating table and hammer out political settlements. They suggested that threat of criminal prosecution can stifle peace efforts, presumably as leaders and warlords facing possible life sentences before International Criminal Court (ICC) calculate that they have nothing to lose by continuing to fight. Mbeki and Mamdani forcefully argued that the mass crimes committed in armed conflicts are political rather than criminal. They suggest it is preferable to suspend questions of criminal accountability until the underlying political problems are resolved. The argument fails to address the rights of victims and fair trial issues. It is a blueprint for impunity.